Large Cell Neuroendocrine Carcinoma of the Bladder with Adenocarcinomatous Component. (6th October 2020) - Halabi, Rami; Abdessater, Maher; Boustany, Johnny; Kanbar, Anthony; Akl, Halim; El Khoury, Joey; El Hachem, Charbel; El Khoury, Raghid
Abstract : Large cell neuroendocrine carcinoma (LCNC) is one of the rarest types of bladder cancer occurring in <1%. Either pure or mixed with another component, it remains one of the most aggressive types of bladder cancer. We report a case of LCNC of the bladder with an adenocarcinomatous component. The patient was a 64-year-old smoker male, who presented for the first time with dysuria and hematuria. A bladder tumor invading the anterior and right lateral bladder walls was discovered, without any secondary localizations. Tumor biopsy showed an LCNC with adenocarcinomatous components. The patient was treated by recurrent tumor resections, chemotherapy, and radiotherapy. No improvement was noted despite close follow-up and adequate treatment. Neuroendocrine bladder tumor is known to have an aggressive, rapid, and disadvantageous evolution. Multiple case reports were published so far, and a recent review was conducted in March 2020 by Sanguedolce et al. (2020). More cases are needed to establish the best management plan for this type of tumor.